PREHEATING EFFECT OF GIOMER’S SURFACE HARDNESS ON DIRECT RESTORATION - Dwiandhono, Irfan; Kurniawan, Aris Aji; Satrio, Rinawati; Logamarta, Setiadi Warata; Winanto, Muthiary Nitzschia Nur Iswary (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Composite resin is a material that is widely used for caries restoration, enamel abrasion, and aesthetic needs because of the good fit with teeth. Restorative materials that release fluoride ions may prolong the therapeutic and protective effects of the enamel. Nowadays, composite resins have been developed a new hybrid restorative material, named giomer. Giomer containing pre-reacted glass-ionomer (PRG) which can release and recharge fluoride ions. Composite resins have a disadvantage, a presence of shrinkage during polymerization, which can cause gaps between the tooth surface and composite resin. Preheating is carried out before irradiation with conventional oven. Preheating makes the composite resin stronger, reduces viscosity makes it easier to adapt and apply, and improves mechanical properties. This study aims to determine the effect of preheating on surface hardness.Method: The research sample used is 27 pieces cylinder-shaped with 5 mm diameter and 2 mm depth. The number of treatments was divided into 3 treatment groups. The treatment groups were divided based on the preheating treatment temperature of 37°C, 60°C, and control group. The surface hardness test was carried out using Vicker's microhardness tester.Result: The statistical One Way ANOVA test showed a significant result between the groups (p<0,05). LSD test (Least Significance Difference test) showed a significant result between the treatment temperature of 37°C, 60°C, and control group (p<0,05).Conclusion: The result of the giomer surface hardness test with preheating showed a higher result than the control group. The preheating group with a temperature of 60°C had the highest result.